Chemical stability and sensory quality of high-oleic garlic-flavored peanuts, salted crispy peanuts, and salted dried peanuts: CHEMICAL STABILITY AND SENSORY QUALITY OF HIGH-OLEIC PEANUTS - CHUN JIAO JIANG,; WEI WEI GAO,; ZHI WEI WANG,; XIU ZHEN WANG,; ZHEN YANG,; HONG WEI HAN,; SHU QI MU,; CHUAN TANG WANG, (Journal of Oilseeds Research, 2024)
High-oleic peanuts have attracted the attention of food processors and consumers for their good keeping quality and purported multiple health benefits. It is of interest to investigate whether high-oleic peanuts can replace their normal-oleic counterparts in Asian style foods. After long-term storage, Huayu 668 garlic-flavored peanuts exhibited a much lower peroxide value, and a comparable or lower acid value as compared with normal-oleic peanuts; the peroxide value of Huayu 668 salted crispy peanuts was on a par with salted dried normal-oleic Tianfu 3 prepared with special shelf life extension processing, while the acid value was more than twice as high. The peroxide value and acid value of all the peanut products herein did not exceed the upper limits specified in China national standard. Significant genotype × storage interactions (garlic flavor and total) and genotype effects (roasted peanut flavor, crunchiness and total) were detected in sensory quality indicators for garlic and salted crispy/dried peanut products, respectively. High-oleic Huayu 668 did not show any disadvantages in terms of organoleptic quality compared to normal-oleic peanuts. The outcome of this study suggested that Huayu 668 could be used for garlic-flavored peanut production and had potential in salted crispy peanut and salted dried peanut processing.